Right from Wrong - McDowell, Josh (Dallas, Tex. Word Publishing, 1994)
According to Josh McDowell, our children are being raised in a society that has largely rejected the concepts of truth and morality. In Right From Wrong, McDowell offers hope and provides families and the church with a sound, thorough, biblical and work
Keywords: Youth ministry; Church work with youth -- United States. Youth -- United States -- Conduct of life. Youth -- Religious life -- United States